Queer difficulty in art and poetry rethinking the sexed body in verse and visual culture - Kim, Jongwoo Jeremy; Reed, Christopher 1961- (Routledge, Taylor & Francis Group, 2018)
Augmenting recent developments in theories of gender and sexuality, this anthology marks a compelling new phase in queer scholarship. Navigating notions of silence, misunderstanding, pleasure, and even affects of phobia in artworks and texts, the essays in this volume propose new and surprising ways of understanding the difficulty—even failure—of the epistemology of the closet. By treating "queer" not as an identity but as an activity, this book represents a divergence from previous approaches associated with Lesbian and Gay Studies. The authors in this anthology refute the interpretive ease of binaries such as "out" versus "closeted" and "gay" versus "straight," and recognize a more opaque relationship of identity to pleasure. The essays range in focus from photography, painting, and film to poetry, Biblical texts, lesbian humor, and even botany. Evaluating the most recent critical theories and introducing them in close examinations of objects and texts, this book queers the study of verse and visual culture in new and exciting ways